Performance Comparison between TCP and UDP Protocols in Different Simulation Scenarios - Taha AL-Dhief, Fahad; Sabri, Naseer; M. Abdul Latiff, N.; Noordini Nik Abd. Malik, Nik; Abbas Abbood Albader, Musatafa; Abed Mohammed, Mazin; Noori AL-Haddad, Rami; Dawood Salman, Yasir; Khanapi Abd Ghani, Mohd; Ibrahim Obaid, Omar (International Journal of Engineering and Technology, 2018)
User Datagram Protocol (UDP) and Transmission Control Protocol (TCP) are a transportation layer routing protocols which are considered of the core protocols of the internet protocol suite. The behaviour of these routing protocols with different network metrics and scenarios is still not very clear. Therefore, this paper presents a comparison of the performance of both TCP and UDP to precisely determine which of these protocols is better. Network Simulator version 2.35 (NS2) is utilized to analyse and evaluate the performance for both TCP and UDP protocols varying in the packet size and the bandwidth. In this study, we have used two scenarios, in the first scenario the bandwidth has been changed with fixed packet size and in the second scenario the packet size has been changed with fixed bandwidth to precisely verify the performance of these protocols. These protocols were examined in terms of the rate end-to-end delay, rate throughput, packet delivery ratio, and packet loss ratioÂ Â